A multimenu system based on the P300 component as a time saving procedure for communication with a brain-computer interface - Jarmolowska, Joanna; Turconi, Marcello M.; Busan, Pierpaolo; Mei, Jie; Battaglini, Piero Paolo (Frontiers in Neuroscience, 2013)
The present study investigates a Brain-Computer Interface (BCI) spelling procedure based on the P300 evoked potential. It uses a small matrix of words arranged in a tree-shaped organization (“multimenu”), and allows the user to build phrases one word at a time, instead of letter by letter. Experiments were performed in two sessions on a group of seven healthy volunteers. In the former, the “multimenu” was tested with a total of 60 choices: 30 “externally-imposed” selections and 30 “free-choice” selections. In the latter, 3 × 3 matrices were compared with 6 × 6 matrices. Each matrix was composed of letters or words, for a total of four matrices. Differences in classifier accuracy, bit rate and amplitude of the evoked P300 were evaluated. Average accuracy in all subjects was 87% with no differences between the selection methods. The 3 × 3 “multimenu” obtained the same level of classifier accuracy as the 6 × 6 matrices, even with a significantly lower amplitude of the P300. Bit rate was increased when using the 3 × 3 matrices compared to the 6 × 6 ones. The “multimenu” system was equally effective, but faster than conventional, letter-based matrices. By improving the speed of communication, this method can be of help to patients with severe difficulties in communication.